Research of distribution pattern of allelic genes and genotypes of C/A polymorphism of COL1A1_1 collagen gene (RS1107946) in children with nasal obstruction of allergic genesis and orthodontic pathology - Shumna, T. Ye.; Kamyshnyi, O. M.; Zinchenko, T. P.; Шумна, Таміла Євгенівна; Камишний, Олександр Михайлович; Зінченко, Тетяна Петрівна; Шумная, Т. Е.; Камышный, А. М.; Зинченко, Т. П. (Запорізький державний медичний університет, 2018)
Purpose. Determination of the genotypes of C/A polymorphism of COL1A1_1 collagen gene (rs1107946) and patterns of distribution of allelic genes in children with nasal obstruction and orthodontic pathology. Materials and methods. A molecular-genetic study for determination of C/A polymorphism of COL1A1_1 collagen gene (rs1107946) was performed in 99 children at the age of 6 to 17 years, for 11 months and 30 days inclusive; 30 children of which had nasal obstruction due to allergic rhinitis without abnormal distal occlusion (the first group); 23 children had just the distal occlusion (the second group); 26 children had allergic rhinitis and distal occlusion (the third group); 20 almost healthy children (the fourth group). Genotyping was performed by the polymerase chain reaction method (Applied Biosystems, USA) using the total DNA samples isolated from whole venous blood using a set of reagents SNP-Screen (Syntol manufacturer) on the CFX96TM Real-Time PCR Detection Systems amplifier (Bio-Rad Laboratories, Inc., USA). Non-parametric statistic methods of the licensed software package Statistica for Windows 6.1.RU, serial number AXXR712D833214SAN5 was used for processing the research results. Results. Molecular-genetic study of the distribution patterns of allelic genes and genotypes of the C/A polymorphism of the COL1A1_1 (rs1107946) collagen gene in the examined children showed that the frequency of occurrence of the C allele was significantly higher than the A allele (71.72 % and 28.28 %, respectively). In this case, the homozygous C/C genotype was registered most often (68.69 %), homozygous genotype A/A (25.25 %) was rarely registered and heterozygous C/A (6.06 %) was very rarely registered. In the observation groups, in children with allergic rhinitis, distal occlusion and a combination of allergic and orthodontic pathology, the genotypes had the following distribution: the C/C genotype – 76.67 %; 34.78 %; 73.00 %; A/A genotype – 20.00 %; 56.52 %; 17.39 %; A/C genotype – 3.33 %; 8.70 %; 11.54 %. The occurrence frequency of alleles of the C/A polymorphism of the COL1A1_1 collagen gene (rs1107946) in the examined children showed that the children with distal occlusion were significantly frequent carriers of A allele (60.87 %), whereas the carriers of C allele were predominantly children with allergic rhinitis (78.33 %), with combined allergic and orthodontic pathology (78.85 %) and healthy (90.00 %), P < 0.05. The correlation between the results of the study conducted in groups of children with the distal occlusion and practically healthy showed that the sensitivity of the presence of A allelic gene was equal to 60.87 %, specificity – 90.00 %, accuracy – 61.54 %. Since the sensitivity and specificity of the diagnostic test exceeded 50.00 %, the prognostic value for the positive result was equal to 87.50 % and for the negative result – 66.67 % and confirm this prognostic significance for the development of the orthodontic pathology in children. This will allow improving the preventive measures in children with orthodontic pathology. Conclusions. The molecular-genetic studies for determining the A allele (rs1107946) of the COL1A1_1 collagen gene in children could be recommended to determine the risk of development and the need for early prevention of the distal occlusion in children. Мета роботи – визначення генотипів поліморфізму С/А гена колагену COL1A1_1 (rs1107946) і закономірностей розподілу алельних генів у дітей із назальною обструкцією алергічного генезу та ортодонтичною патологією. Матеріали та методи. Молекулярно-генетичне дослідження для визначення поліморфізму С/А гена колагену COL1A1_1 (rs1107946) здійснили у 99 дітей віком від 6 до 17 років, 11 місяців 30 днів включно; із них 30 дітей з назальною об¬струкцією внаслідок алергічного риніту без аномального дистального прикусу (І група); 23 дитини тільки з дистальним прикусом (ІІ група спостереження); 26 дітей з алергічним ринітом та дистальним прикусом (ІІІ група спостереження); 20 практично здорових дітей (ІV, контрольна група). Генотипування виконали методом полімеразної ланцюгової ре¬акції згідно з інструкцією (Applied Biosystems, USA) з використанням зразків тотальної ДНК, котра виділена з цільної венозної крові, з використанням набору реагентів «SNP-Скрін» (виробник «Syntol») на ампліфікаторі CFX96TM Real- Time PCR Detection Systems (Bio-Rad Laboratories, Inc., USA). Для статистичного аналізу результатів дослідження використали непараметричні методи статистики ліцензійного пакета програм Statistica for Windows 6.1.RU, серійний номер АХХR712D833214SAN5. Результати. Молекулярно-генетичне дослідження закономірностей розподілу алельних генів і генотипів поліморфізму С/А гена колагену COL1A1_1 (rs1107946) в обстежених дітей показало, що частота виявлення алеля С була вірогідно більшою, ніж алеля А (71,72 % та 28,28 % відповідно). При цьому найбільш часто реєстрували гомозиготний генотип С/С (68,69 %), рідше – гомозиготний генотип А/А (25,25 %) і дуже рідко – гетерозиготний С/А (6,06 %). У групах спо¬стереження у дітей з алергічним ринітом, дистальним прикусом і з поєднанням алергічної та ортодонтичної патологій генотипи мали такий розподіл: генотип С/С – 76,67 %; 34,78 %; 73,00 %; генотип А/А – 20,00 %; 56,52 %; 17,39 %; генотип А/С – 3,33 %; 8,70 %; 11,54 %. Аналіз частоти виявлення алелей поліморфізму С/А гена колагену COL1A1_1 (rs1107946) показав: діти з фенотиповими ознаками дистального прикусу вірогідно частіше були носіями алеля А (60,87%), а носіями алеля С переважно були діти з алергічним ринітом (78,33 %), з поєднаною алергічною та орто¬донтичною патологіями (78,85 %) і здорові (90,00 %), р < 0,05. Прогностична чутливість наявності алельного гена А в розвитку дистального прикусу в дітей становила 60,87 %, специфічність – 90,00 %, точність – 61,54 % (перевищували 50,00 %), прогностична цінність для позитивного результату становила 87,50 %, для від’ємного – 66,67 %, що під-тверджувало його прогностичну значущість у визначенні ризику розвитку ортодонтичної патології в дітей із наданням більшої можливості рано й ефективно вживати профілактичні заходи. Висновки. Молекулярно-генетичне дослідження з визначенням алеля А (rs1107946) гена колагену COL1A1_1 у дітей можна рекомендувати для визначення ризику розвитку та необхідності ранньої профілактики дистального прикусу в дітей. Цель работы – определение генотипов полиморфизма С/А гена коллагена COL1A1_1 (rs1107946) и закономерностей распределения аллельных генов у детей с назальной обструкцией аллергического генеза и ортодонтической патологией. Материалы и методы. Молекулярно-генетическое исследование для определения полиморфизма С/А гена коллагена COL1A1_1 (rs1107946) проведено у 99 детей в возрастеот 6 до 17 лет, 11 месяцев, 30 дней включительно; из них 30 детей с назальной обструкцией аллергического генеза без аномального дистального прикуса (І группа); 23 ребенка только с дистальным прикусом (ІІ группа); 26 детей с аллергическим ринитом и дистальным прикусом (ІІІ группа); 20 практически здоровых детей (ІV, контрольная группа). Генотипирование проведено методом полимеразной цепной реакции согласно инструкции (Applied Biosystems, USA) с использованием образцов тотальной ДНК, выделенной из цельной венозной крови, с использованием набора реагентов «SNP-Скрин» (производитель «Syntol») на амплификаторе CFX96TM Real-Time PCR Detection Systems (Bio-Rad Laboratories, Inc., USA). Для статистического анализа результатов исследования использованы непараметрические методы статистики лицензионного пакета программ Statistica for Windows 6.1.RU, cерийный номер АХХR712D833214SAN5. Результаты. Молекулярно-генетическое исследование закономерностей распределения аллельных генов и генотипов полиморфизма С/А гена коллагена COL1A1_1 (rs1107946) у обследованных детей показало, что частота встречаемо¬сти аллеля С была достоверно выше, чем аллеля А (71,72 % и 28,28 %, соответственно). При этом наиболее часто регистрировали гомозиготный генотип С/С (68,69 %), реже был выявлен гомозиготный генотип А/А (25,25 %), очень редко – гетерозиготный С/А (6,06 %). В группах наблюдения у детей с аллергическим ринитом, дистальным прикусом и сочетанием аллергической и ортодонтической патологий генотипы имели следующее распределение: генотип С/С – 76,67 %; 34,78 %; 73,00 %; генотип А/А – 20,00 %; 56,52 %; 17,39 %; генотип А/С – 3,33 %; 8,70 %; 11,54 %. Анализ частоты встречаемости аллелей полиморфизма С/А гена коллагена COL1A1_1 (rs1107946) показал: дети с фенотипи¬ческими признаками дистального прикуса достоверно чаще были носителями аллеля А (60,87 %), а носителями аллеля С преимущественно были дети с аллергическим ринитом (78,33 %), с сочетанной аллергической и ортодонтической патологией (78,85 %) и здоровые (90,00 %), р < 0,05. Прогностическая чувствительность наличия аллельного гена А в развитии дистального прикуса у детей составила 60,87 %, специфичность – 90,00 %, точность – 61,54 % (превышали 50,00 %), прогностическая ценность для положительного результата составила 87,50 %, для отрицательного – 66,67 %, что подтверждало его прогностическую значимость при определении риска развития ортодонтической патологии у детей для более раннего и эффективного проведения профилактических мероприятий. Выводы. Молекулярно-генетическое определение аллеля А (rs1107946) гена коллагена COL1A1_1 у детей может быть рекомендовано для определения риска развития и необходимости ранней профилактики дистального прикуса у детей.
Дослідження закономірностей розподілу алельних генів і генотипів поліморфізму С/А гена колагену COL1A1_1 (rs1107946) у дітей із назальною обструкцією алергічного генезу та ортодонтичною патологією
Исследование закономерностей распределения аллельных генов и генотипов полиморфизма С/А гена коллагена COL1A1_1 (rs1107946) у детей с назальной обструкцией аллергического генеза и ортодонтической патологией
Keywords: alleles; genotype; collagen; distal occlusion; allergic rhinitis; children; алельні гени; генотип; колаген; дистальний прикус; алергічний риніт; діти; аллельные гены; коллаген; аллергический ринит; дети